PENERAPAN MODEL INQUIRY TRAINING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA PADA MATERI CAHAYA DAN ALAT OPTIK DI KELAS VIII SMP NEGERI 25 PEKANBARU - Manurung, Lamria Sri; Azhar, Azhar; Nasir, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study was aimed at determining the differences of student learn by science process skills applied an inquiry training model with classes that applied conventional learning to light and optical materials of second grade students of SMPN 25 Pekanbaru. The type of this research is quasi eksperimental with two-group posttest-only design. The study population was all second grade students of SMP Negeri 25 Pekanbaru in the Academic Year 2018/2019 which totaled 381 students and the study sample amounted to 78 students. The research instrument used was a matter of testing students' science process skills. The data collection technique in this study was to provide a test with indicators of science process skills after the learning process was carried out. In this study, the data were analyzed by evaluating students’ absorption and effectiveness, and inferential analysis of hypothesis testing by means of a t-test. The results of this study are the absorption capacity of the experimental class of 78.13% in the good category and the control class at 69.08% in the fairly good category with a value difference of 9.05%. The effectiveness of learning in the experimental class is in the effective category and the control class is in the quite effective category. Based on the t-test obtained a significant value (2-tailed) of 0.01 <0.05 which explains that there is a significant difference between the science process skills of students who apply the inquiry training model and those who apply conventional learning.Key Words: Science Process Skills, Inquiry Training, Light and Optical Instruments